A new trend in the medication of hepatocyte cytoxicity in mice: protective role of probiotic bacteria - Allam, Nanis G.; El-Sheekh, Mostafa M.; Sarhan, Naglaa I.; Alfakharany, Ghada S. (Environmental science and pollution research international, 2021)
Liver toxicity is affected by several factors, including certain medications, fumes emission from factories, materials used in industries, and exposure to chemicals such as carbon tetrachloride (CCl 4 ). Some preselected probiotic bacteria strains have been widely employed in different medical researches due to their antioxidant, anticancer, antimicrobial, anti-inflammatory characters, and hepatoprotective factor. The present study was aimed to evaluate the protective role of probiotic bacteria ( Lactobacillus plantarum DSMZ 20174) and their ameliorative effects against CCl 4 -induced hepatotoxicity in mice. The cell cycle of hepatocytes and the expression of transforming growth factor-β (TGF-β) were assessed by flow cytometry as indicators for apoptosis. The antioxidant activity of probiotic bacteria was estimated by measuring lipid peroxidation (LPO) and scavenging 2,2-diphenyl-1-picryl-hydrazyl (DPPH). The results showed that the treatment of CCl 4 -administered mice by supernatant from Lactobacillus plantarum DSMZ 20174 induced an amelioration in CCl 4 -induced increases in serum activity of the liver enzymes and decreases in LPO and DPPH. After treatment with probiotics, the liver histopathological studies showed abundant infiltration and accumulation of mononuclear cells and fibroblast, indicating a positive effect ameliorating the damage previously induced by CCl 4 . In sum, the results of the present work indicate the protective effects of Lactobacillus plantarum against hepatotoxicity through antioxidant effects.